Natural immunity in mice to structural polypeptides of endogenous type C RNA viruses. - Stephenson, J R (1976)
The immunological responses of inbred mice to structural components of one class of endogenous virus were investigated by means of radioimmunoassays utilizing highly purified viral proteins. Naturally occurring antiviral antibodies were demonstrated only in those strains possessing information for induction of a mouse cell-tropic endogenous virus. Moreover, these antibodies invariably appeared subsequent to the detection of spontaneous replication of this virus in the same animal. The immune responses elicited were much stronger against endogenous viral gp70 than p30, consistent with previous findings of tolerance in the mouse to the major structural antigen of its endogenous virus. However, the demonstration of an immune response to p30 under conditions of both natural and experimental immunization establishes that tolerance to this viral antigen can be overcome.